Why do people buy insurance? A modern answer to an old question - Markus Rieger-Fels (Risk Management and Insurance Review, 2024)
Three archetypical models of insurance demand based, respectively, on risk aversion, state-dependent marginal utility, and imperfectly divisible consumption are presented. These models show that the common principle underlying insurance is not always a risk transfer but meeting a conditional need. In general, insurance aligns the risk in one's financial endowment with the risk in one's financial needs. This extension of the traditional view of insurance allows simple generalizations of classic results, has implications for policy advice, and may help guiding further research.
Keywords: 330